Pengembangan Bisnis Model Cnvas untuk Meningkatkan Pendapatan (Fotokopi Mandiri di Kabupaten Pasuruan) - Afifatus Salwa; Eka Farida; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to analyze the implementation of the Business Model Canvas (BMC) and its contribution to increasing the revenue of Fotokopi Mandiri, a micro and small enterprise operating in Pasuruan Regency. The research focuses on examining the application of the nine core elements of the BMC, formulating revenue enhancement strategies, and evaluating the impact of BMC implementation on business revenue performance. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, focus group discussions (FGD), and documentation. The informants consisted of the business owner, employees, and customers who were directly involved in business operations. The findings indicate that the implementation of the BMC supports more structured and systematic business management. Among the nine elements, four components—value proposition, Customer relationships, Channels, and revenue streams—play a dominant role in driving revenue growth. The application of the BMC positively influences business performance through improved operational efficiency, strengthened marketing strategies, enhanced service quality, and more effective resource utilization. Furthermore, BMC implementation contributes to business sustainability by increasing production capacity and supporting the adoption of digital technology in service delivery and promotion. Overall, this study demonstrates that the Business Model Canvas is an effective strategic tool for improving revenue performance and ensuring the sustainability of micro-scale service enterprises, particularly in the photocopy and printing service sector. Keywords: Business Model Canvas, Revenue Growth, Micro And Small Enterprises, Photocopy Services, Business Sustainability